The New Value Controversy and the Foundations of Economics - Freeman, Alan .; Kliman, Andrew; Wells, Julian (Cheltenham : Edward Elgar, 2002)
This book assembles an excellent set of mutually engaged articles.The articles document the dramatic recent renewal of Marxian value theories, extend them provocatively to important issues, and thereby effectively challenge Marxian economics' censorious exclusion from the academic mainstream.
Includes bibliographical references and index.
aia 10/09/13
Loan
Keywords: Value; Economics